The Sociological Imagination: Do We Build Boundaries or Do We Want Solidarity? - Romana Marková Volejníčková; Markéta Švarcová; Alena Křížková; Lenka Formánková (Gender a Výzkum, 2019)
Report from the conference Europe and Beyond: Boundaries, Barriers and Belonging.